Proceedings of the 36th International ACM SIGIR Conference on Research and Development in Information Retrieval 2013
DOI: 10.1145/2484028.2484060
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment diversification with different biases

Abstract: Prior search result diversification work focuses on achieving topical variety in a ranked list, typically equally across all aspects. In this paper, we diversify with sentiments according to an explicit bias. We want to allow users to switch the result perspective to better grasp the polarity of opinionated content, such as during a literature review. For this, we first infer the prior sentiment bias inherent in a controversial topic -the 'Topic Sentiment'. Then, we utilize this information in 3 different ways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…It aims to improve user satisfaction by providing a diverse view of information, thereby increasing the probability of returning some information that truly matches the user's expectation. Various applications that have benefited from diversification include sentiment analysis [4], web search [12], database search [7], largescale visualization [31], social network [40] and recommender systems [11]. In our case, since users cannot often precisely and exhaustively describe their queries, increasing diversity of tag-query suggestion will provide users more chances to find the desired papers quickly.…”
Section: Related Workmentioning
confidence: 99%
“…It aims to improve user satisfaction by providing a diverse view of information, thereby increasing the probability of returning some information that truly matches the user's expectation. Various applications that have benefited from diversification include sentiment analysis [4], web search [12], database search [7], largescale visualization [31], social network [40] and recommender systems [11]. In our case, since users cannot often precisely and exhaustively describe their queries, increasing diversity of tag-query suggestion will provide users more chances to find the desired papers quickly.…”
Section: Related Workmentioning
confidence: 99%
“…Martineau et al [14] proposed the metric D-TFIDF to weight words scores. Martineau et al found that D-TFIDF improved the classification accuracy of subjective sentences in the Pang and Lee subjectivity dataset 1 . Moreover, variants of our proposed method outperformed the static lexicons with D-TFIDF showing similar performance.…”
Section: Experiments: Opinion Classificationmentioning
confidence: 99%
“…Later, Jo and Oh [13] proposed a unified aspect and sentiment model based on the assumption that each sentence concerns one aspect and all sentiment words in that sentence refer to that sentence. Finally, Aktolga and Allan [1] targeted the task of sentiment diversification in search results. The common element among these works [1,9,13,28] is the use of the sentiment lexicon SentiWordNet [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations